Coexpression of SFRP1 and WIF1 as a Prognostic Predictor of Favorable Outcomes in Patients with Colorectal Carcinoma. (14th May 2014) - Huang, Shiyong; Zhong, XiaoMing; Gao, Jun; Song, Rongfeng; Wu, Hongyu; Zi, Shuming; Yang, Shijie; Du, Peng; Cui, Long; Yang, Chun; Li, Zikang
Abstract : Colorectal tumorigenesis is ascribed to the activity of Wnt signaling pathway in a ligand-independent manner mainly through APC and CTNNB1 gene mutations and in a ligand-dependent manner through low expression of Wnt inhibitors such as WNT inhibitory factor 1 (WIF1) and secreted frizzled related protein 1 (SFRP1). In this study we found that WIF1 protein expression was increased and SFRP1 was decreased significantly in CRC tissue versus normal tissue, and high expression of WIF1 was associated with big tumor diameters and deep invasion, and loss of SFRP1 expression was associated with the left lesion site, deep invasion, and high TNM stage. Among the four expression patterns (WIF+/SFRP1+, WIF+/SFRP1−, WIF−/SFRP1+, and WIF−/SFRP1−) only coexpression of WIF1 and SFRP1 (WIF+/SFRP1+) was associated with favorable overall survival, together with low TNM stage, as an independent prognostic factor as shown in a multivariate survival model. The results indicated that WIF1 seemed to play an oncogenic role, while SFRP1 seemed to play an oncosuppressive role although both of them are secreted Wnt antagonists. Coexpression of SFRP1 and WIF1, rather than SFRP1 or WIF1 alone, could be used, together with low TNM stage, as a prognostic predictor of favorable outcomes in CRC.